Motor control of downward object-transport movements with precision grip by object weight. (2nd April 2016) - Yamamoto, Shinji; Shiraki, Yoshihide; Uehara, Shintaro; Kushiro, Keisuke
Abstract: In the present study, we investigated the kinematics of object-transport movement in a downward direction using a precision grip, to elucidate how the central nervous system (CNS) takes into account object weight when making the movement, even when participants are unable to recognize the weight until they grasp the object. We found that the kinematics during transport movement were significantly changed by the object weight, even when the weight was unrecognized visually, suggesting that the CNS controls object-transport movement in a downward direction according to object weight, regardless of the visual recognizability of the weight.